Friendship and Technology: A Philosophical Approach to Computer Mediated Communication - Petricini, Tiffany (Routledge Research in Communication Studies, 2022)
This book explores the nature of technology – participatory media in particular – and its effects on our friendships and our fundamental sense of togetherness. Situating the notion of friendship in the modern era, the author examines the possibilities and challenges of technology on our friendships. Taking a media ecology approach to interpersonal communication, she looks at issues around phenomenology, recognition of friends as unique, hermeneutics in a digital world and mediated communication, social dimensions of time and space, and communication ethics. Examining friendship as a communicative phenomenon and exploring the ways in which it is created, sustained, managed, produced, and reproduced, this book will be relevant to scholars and students of interpersonal communication, mediated communication, communication theory and philosophy, and media ecology. This book is freely available as a downloadable Open Access PDF under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license. https://www.taylorfrancis.com/books/mono/10.4324/9781003188810/friendship-technology-tiffany-petricini